From Viral to Protection: Do Parents Take Action? - Muqimah Surganingsih; Fitriani Dzulfadhilah; Hasmawaty Hasmawaty; Bonita Mahmud (Universitas Trunodjoyo Madura, 2026)
The rapid advancement of digital technology has expanded young children’s access to information while simultaneously increasing the risk of exposure to inappropriate online content, as illustrated by the viral “Incest Fantasy” case. This study aims to measure parents’ awareness of the case, explore their emotional and psychological responses, analyze changes in protective behavior, and identify additional preventive actions in the context of child protection in the digital era. Employing a descriptive quantitative design, the study involved 37 parents of kindergarten children (n=37) selected using purposive sampling. Data were collected using a Likert-scale questionnaire measuring parental awareness, emotional and psychological responses, protective behavior changes, and preventive actions, and analyzed through descriptive statistics and Pearson correlation. The findings indicate that although parents demonstrated relatively high levels of awareness, awareness was not significantly associated with changes in protective behavior or preventive actions. In contrast, emotional and psychological responses exhibited a very strong positive correlation with changes in protective behavior (r = 0.814, p 0.01) and a moderate, significant correlation with additional preventive actions (r = 0.542, p 0.01). These results suggest that emotional engagement plays a more decisive role than cognitive awareness in shaping parents’ protective behaviors toward their children. This study underscores the importance of integrating cognitive, affective, and humanistic dimensions in the design of digital child protection programs to strengthen parental involvement and responsiveness.